PENGARUH AKUPUNKTUR TITIK LI11, ST36, DAN TITIK LOKAL KASUS DERMATITIS ATOPIK PADA SANTRI DI PONDOK DARUL IHSAN SRAGEN - Fatimah Rahmawati; Anisa Andriani; Yessy Widhi Astuti; Franciscus Xaverius; Fatimah Hasna Karima; Utami Pangestu (Jurnal Medicare, 2026)
Dermatitis is an inflammatory skin disorder caused by a type IV cell-mediated hypersensitivity reaction following disruption of the skin barrier by specific antigens. Various factors, including age, sex, environmental conditions, personal hygiene, clothing, cosmetics, and topical medications, contribute to its occurrence. This study aimed to evaluate the effect of acupuncture at LI11, ST36, and local points on reducing dermatitis lesion severity among students at the Darul Ihsan Muhammadiyah Islamic Boarding School, Sragen. A pre-experimental one-group pretest–posttest design was employed from October to November 2025. Of 425 boarding school students, 150 had a history of dermatitis, and 30 participants met the inclusion criteria. Dermatitis severity was assessed using the SCORAD questionnaire and observation sheets before and after treatment. Data were analyzed using the Wilcoxon signed-rank test with a significance level of 0.05. The results showed a significant reduction in dermatitis lesion severity (p = 0.001), indicating that acupuncture may serve as a safe, non-pharmacological complementary therapy for dermatitis.